Using Quality Database Convert the Quantity data into Quality data and Automate the Control Points using SURF Algorithm in Spatio-Temporal data - Rathee, Sonia; Rishi, Rahul (International Journal of Computer Sciences and Engineering, 2025)
GIS data can be divided into two formats, raster and vector. Raster format can represent the values which give quantitative information such as temperature, vegetation intensity, land use/cover etc. Vector format can represent the value which give qualitative data which consists of point, lines and polygons and these representing the location, distance or area of landscape features in graphical forms. For extracting the data we can register the image for the initial processing. For register the image we can select the control points. This control point selection can convert the quantity data into quality data. This process of transforming information (quantity) into knowledge (quality) is called appropriation. To overcome the limitations of relational databases and provide a greater knowledge in terms of knowledge we use the spatio-temporal database.